2004
DOI: 10.1159/000076587
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid, Phosphate and Oxalate Stones: Treatment and Prophylaxis

Abstract: Medical treatment for the most commonly encountered types of renal stones is described. Nowadays treatment for uric acid stones is well-defined: alkalinizing urine is easy with drugs that are sufficiently active and well enough managed. Relapse is avoided in a high percentage of patients. Medical treatment of phosphate or calcium stones is a more open question as results are far from satisfactory compared with intra- and extra-corporeal approaches which are often minimally invasive and well accepted by both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Recently, there was emerging evidence indicating that uric acid calculi became more prevalent among patients with obesity, T2DM, and metabolic syndrome [ 11 , 25 ]. This suggested that the pathogenetic formation of uric acid calculi could not merely be derived from abnormalities in uric acid metabolism but also be attributed to dietary habits and lifestyle [ 26 , 27 ]. According to the literature, uric acid calculi were associated with obesity, metabolic syndrome, and T2DM [ 11 13 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there was emerging evidence indicating that uric acid calculi became more prevalent among patients with obesity, T2DM, and metabolic syndrome [ 11 , 25 ]. This suggested that the pathogenetic formation of uric acid calculi could not merely be derived from abnormalities in uric acid metabolism but also be attributed to dietary habits and lifestyle [ 26 , 27 ]. According to the literature, uric acid calculi were associated with obesity, metabolic syndrome, and T2DM [ 11 13 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical experiments, it was confirmed that Rowatinex has antilithogenic, antibacterial, anti-inflammatory, spasmolytic, and analgesic properties [14, 15]. The antilithogenic property, which influences renal oxalate lithogenesis, is important because most urinary stones are composed of calcium oxalate aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…1 = Continental breakfast/soup/soup; 2 = fasting/ fasting/fasting; 3 = fasting/fasting/dinner; 4 = continental breakfast/lunch/soup; 5 = continental breakfast/lunch/dinner; 6 = fasting/lunch/dinner. further treatment or other measures are needed to render the patients stone free [3,[12][13][14] . Retreatment rates after primary ESWL are significantly correlated with stone burden and location.…”
Section: Discussionmentioning
confidence: 99%